Experimental study of a hemispherical three-dimensional solar collector operating with silver-water nanofluid. (April 2021) - Moravej, Mojtaba; Doranehgard, Mohammad Hossein; Razeghizadeh, Alireza; Namdarnia, Fatemeh; Karimi, Nader; Li, Larry K.B.; Mozafari, Hamid; Ebrahimi, Zohreh
Abstract: In this experimental study, a fixed three-dimensional solar collector with a hemispherical geometry has been evaluated in accordance with ASHRAE standards. The collector features spiral tubes that transport fluid from the inlet to the outlet with no riser. Pure water and Ag-water nanofluid at different nanoparticle concentrations (0.1, 0.2 and 0.3%) and different flow rates (0.1–0.6 GPM) were tested under different environmental conditions (temperature and radiation). The results show that this hemispherical solar collector, owing to its geometry and the specific arrangement of its pipes in relation to the overall surface area, exhibits promising thermal performance, making it a viable candidate for both domestic and industrial deployment. The average increase in efficiency when switching from water to Ag-water nanofluid was found to be around 11%, with the maximum efficiency (61.1%) occurring at a nanoparticle concentration of 0.3% and a flow rate of 0.6 GPM.